2021
DOI: 10.1017/s0007114521004116
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Score for Visceral Fat: a novel predictor for the risk of type 2 diabetes mellitus

Abstract: To investigate the association between the Metabolic Score for Visceral Fat (METS-VF) and risk of type 2 diabetes mellitus (T2DM) and compare the predictive value of the METS-VF for T2DM incidence with other obesity indices in Chinese people. A total of 12,237 non-T2DM participants aged over 18 from the Rural Chinese Cohort Study of 2007-2008 were included at baseline and followed up during 2013-2014. The cox proportional hazards regression was used to calculate hazard ratios (HRs) and 95% confidence intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“… 31 A cohort study from Henan (China), revealed METS-VF to be positively correlated with the risk of hypertension and type-2 diabetes mellitus. 32 , 33 In our study, with an increase in METS-VF quartile, CKD risk increased gradually, reaching 29.19% in Q4. Compared with Q1, the CKD risk increased by 3.04-times in Q4.…”
Section: Discussionsupporting
confidence: 51%
“… 31 A cohort study from Henan (China), revealed METS-VF to be positively correlated with the risk of hypertension and type-2 diabetes mellitus. 32 , 33 In our study, with an increase in METS-VF quartile, CKD risk increased gradually, reaching 29.19% in Q4. Compared with Q1, the CKD risk increased by 3.04-times in Q4.…”
Section: Discussionsupporting
confidence: 51%
“…In their study, Yu et al discovered that the METS-VF had a robust predictive capacity for chronic kidney disease (CKD) when in comparison to alternative evaluation markers of central adiposity [ 43 ]. Additionally, in comparison to other evaluation indicators of obesity, METS-VF demonstrates reliability and applicability as a predictor of hypertension and diabetes within the Chinese population [ 44 , 45 ]. A 36,876-person study found a favorable correlation between METS-VF and asthma [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the METS-VF was reported to have the ability to provide relatively accurate measurements of visceral adiposity and insulin resistance even in metabolically healthy obese individuals who do not have substantial laboratory disturbances ( 17 ). Meanwhile, the METS-VF has been demonstrated to be a strong predictor for hypertension and diabetes in Western and Chinese populations, and has stronger predictive power than several of the abovementioned indices ( 17 , 32 , 33 ). Overall, these characteristics and advantages of the METS-VF may facilitate its use in CKD risk prediction.…”
Section: Discussionmentioning
confidence: 99%